Current Immunotherapeutic Strategies to Enhance Oncolytic Virotherapy - Meyers, Daniel E.; Wang, Amanda A.; Thirukkumaran, Chandini M.; Morris, Don G. (Frontiers in Oncology, 2017)
Oncolytic viruses (OV) represent a promising strategy to augment the spectrum of cancer therapeutics. For efficacy, they rely on two general mechanisms: tumor-specific infection/cell-killing, followed by subsequent activation of the host’s adaptive immune response. Numerous OV genera have been utilized in clinical trials, ultimately culminating in the 2015 FDA approval of a genetically engineered herpes virus, Talminogene laherparepvec (T-Vec). It is generally accepted that OV as monotherapy have only modest clinical efficacy. However, due to their ability to elicit specific antitumor immune responses, they are prime candidates to be paired with other immune-modulating strategies in order to optimize therapeutic efficacy. Synergistic strategies to enhance the efficacy of OV include augmenting the host antitumor response through the insertion of therapeutic transgenes like GM-CSF, utilization of the prime-boost strategy, and combining OV with immune modulatory drugs such as cyclophosphamide, sunitinib and immune checkpoint inhibitors. This review provides an overview of these immune-based strategies to improve the clinical efficacy of oncolytic virotherapy.